The use of the autstaffing for reducing the risks of the staffs activity - Romanenko, Mariia (Skhid, 2013)
In the article there are examined the main reasons for the use of autstaffing with the purpose to reduce the risk of the staffs activity; there is offered our own order of autstaffing; there is developed a scheme of the complex services autstaffing providing; there is formed a triangle of possibilities for the application of the autstaffing to reduce or to avoid the risk of the staffs activity.